HRQOL related to urinary diversion in Radical Cystectomy: a systematic review of recent literature - Pazeto,Cristiano Linck (2019)
ABSTRACT Introduction: The health-related QoL is a patient-centered evaluation covering several aspects. This evaluation seems to be particularly important in patients submitted to radical cystectomy (RC) and urinary diversion with ileal conduit (IC) or a neobladder (NB). Objective: Review all recent data comparing QoL outcomes after radical cystectomy with NB and IC diversions. Evidence Acquisition: A systematic search in PubMed/Medline, Embase, and Cochrane databases was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) statement in December 2018. All articles published from January 01, 2012 to December 31, 2018, were included. A study was considered relevant if it compared QoL outcomes using validated questionnaires (EORTC QLQ C30, FACT-G, FACT-BL, FACT-VCI, and BCI). Evidence Synthesis: In 11 included studies, a total of 1389 participants were accounted (730 NB and 659 IC cases). The studies were conducted in 8 different countries, two were prospective, and none was randomized. There were two studies favoring results with a neobladder, 3 with incontinent diversion and 6 with no differences. The EORTC-QLQ-C30 was the most used instrument (5 studies) followed by FACT VCI and BCI (3 studies each). Given the heterogeneity of data and lack of prospective studies, a meta-analysis was not performed. Conclusion: No superiority of one urinary diversion was characterized. It seems that the choice must be individualized with an extensive preoperative orientation of the patient and their relatives. That will probably influence how the patient accepts the new condition.